Extracting Software Features From Online Reviews To Demonstrate Requirements Reuse In Software Engineering - Bakar, NH; Kasirun, ZM; Salleh, N; Halim, AH (Univ Utari Malaysia-Uum, 2024)
Indexed by WOS